ISPC Assessment of the Grain Legumes and Dryland Cereals Agri-food Systems - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
ISPC Assessment of the Grain Legumes and Dryland Cereals Agri-food Systems CRP-II revised proposal (2017-2022). GLDC aims to increase the productivity, profitability, resilience, and marketability of critical and nutritious grain legumes (chickpea, cowpea, pigeonpea, groundnut, lentil, soybean) and cereals (sorghum, pearl millet, finger millet) grown within the semi-arid and sub-humid dryland agro-ecologies of SSA and SA.